Downregulating STAT1/caspase‐3 signaling with fludarabine to alleviate progression in a rat model of steroid‐induced avascular necrosis of the femoral head. Issue 4 (1st December 2018) - Lin, Jian; Qi, Weihui; Chen, Kai; Yan, Yingzhao; Li, Xiaobin; Feng, Zhenhua; Pan, Xiaoyun
Abstract: Steroid‐induced avascular necrosis of the femoral head (SANFH) is mainly induced by glucocorticoids. Fludarabine (Flu) is a specific signal transducer and activator of transcription 1 (STAT1) inhibitor. In this study, we investigated the effect of Flu on SANFH and the role played by the STAT1/caspase‐3 signaling pathway. Sprague‐Dawley rats were divided into control, SANFH, and Flu‐treated SANFH groups. Femoral head tissues were collected for hematoxylin‐eosin (H&E) staining and Western blot analysis. The latter was used to measure the levels of stat1, phospho‐stat1, caspase‐3, cleaved caspase‐3, caspase‐9, cleaved caspase‐9, Bax, cytochrome C, Bak, B‐cell lymphoma‐extra large, and B‐cell lymphoma‐2 protein expression. The results showed that Flu regulates protein expression in dexamethasone (Dex)‐induced SANFH. H&E staining showed a decrease in the ratio of empty lacunae induced by Dex. Taken together, our study demonstrated the involvement of the STAT1/caspase‐3 signaling pathway in SANFH and the potential of Flu as a therapeutic agent for patients with SANFH.